Digestive tract contents in light lambs as affected by forage inclusion and weaning - Álvarez-Rodríguez J.; Sanz A.; Blasco I.; Ripoll R.; Joy M. (Challenging strategies to promote the sheep and goat sector in the current global context, 2011)
The effects of forage inclusion (alfalfa-fed with concentrate supplementation, ALF, vs concentratefed, CONC) and milk supply (suckling until 13 kg, W, vs until slaughter, S) on the digestive tract contents of Rasa Aragonesa light lambs (n=32, target slaughter weight of 23.0 kg) were analysed in a 2 x 2 factorial design. Immediately after slaughter (without fasting period), the contents of each gastrointestinal compartment were separated and weighed and pH of reticule-rumen and caecum were measured. Age at slaughter and empty body-weight did not differ (P>0.05) among treatments (94 days and 19.9 kg). Reticule-rumen content was similar in CONC lambs (1749 g) but it was higher (P<0.05) in ALF-W than in ALF-S (2174 vs 1385 g). The abomasum content did not differ (P>0.05) among treatments (188 g), nor did the small intestine content (421 g, P>0.05). The caecum content was similar in CONC (221 g) but it was greater (P<0.05) in ALFW than in ALF-S (408 vs 231 g). The large intestine content was lower (P<0.001) in CONC than in ALF (118 vs 181 g). Overall digestive tract content was similar in CONC (2667 g) but it was greater (P<0.05) in ALFW than in ALF-S (3581 vs 2378 g). Weaned but not suckling lambs raised on alfalfa filled more their digestive tracts than the rest, which also involved a more buffered digestive environment.
13. International Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2009/10/14-16, León (Spain)